Difference in Anxiety between Left and Right Hemispheric Lesions of Ischemia among Patients with Stroke at Dr. Moewardi Hospital - Shofri, M Maulana; Hartanto, O S; Murti, Bhisma (Indonesian Journal of Medicine, 2016)
Background: The difference of lesion location and anxiety usually manifests into different signs and symptomps based on the patientÃ¢â¬â¢s lesion location. This study aimed to determine the difference in anxiety between left and right hemispheric lesions of ischemia among patients with stroke.Subjects and Method: This was an analytic observational study with cross sectional design. A total sample of 30 patients with stroke consisting of 15 patients with left hemisphere lesion and 15 patients with right hemisphere lesion of ischemia was selected by random sampling. Anxiety was assessed using Hamilton Rating Scale for Anxiety (HRSA) questionnaire. The data were analyzed by multiple linear regression.Results: After controlling for family supports as confounding factor, this study showed significantly lower anxiety in patients with left hemispheric lesion ischemia than patients right hemispheric lesion (b= -2.77; p = 0.039). Family support lessened anxiety among patients with stroke (b=-5.21; p=0.003).Conclusion: Anxiety in stroke patients with left hemispheric lesion of ischemia is lower than stroke patients with right hemispheric lesion.Keywords: anxiety, ischemic stroke, left hemispheric lesion, right hemispheric lesionCorrespondence:ÃÂ M. Maulana Shofri. Faculty of Medicine, Sebelas Maret University, Surakarta.Indonesian Journal of Medicine (2016), 1(3): 146-151https://doi.org/10.26911/theijmed.2016.01.03.01